PENGEMBANGAN BAHAN AJAR BERBASIS BUDAYA MELAYU SERDANG BEDAGAI UNTUK MENINGKATKAN PEMAHAMAN KONSEP BANGUN DATAR KELAS IV SD - Sukmawarti, Sukmawarti; Irawan, Ira Fauziah; Firmansyah, Firmansyah (JURNAL PENELITIAN PENDIDIKAN MIPA, 2025)
The purpose of this research is to determine the development and feasibility of teaching materials based on Serdang Bedagai Malay culture in increasing understanding of the concept of flat shapes in class IV elementary school. Research and Development (R&D) researchers. The test subjects in this research were material experts, teaching materials experts, and learning experts. The object of this research is flat-shape teaching materials based on Malay culture which are suitable for use in the flat-shape material mathematics learning process in class IV. The final validation results from material experts obtained a score of 85. From learning experts obtained a score of 87.6 and from learning experts a score of 89. The average of the assessments of the three experts obtained a score of 87.2. From this score it can be said that the flat-rise teaching materials based on Malay culture that were developed are "very suitable" for use in the learning process.